Electrically elicited quadriceps muscle torque: Comparison at three knee angles. (3rd June 2021) - Scott, Wayne; Adams, Cheryl; Fisher, Jason; Fisher, Stephanie; Jones, Kayla; Mathieu, Brian
ABSTRACT: Background and Purpose : The effect of knee angle on electrically elicited quadriceps muscle torque has not been established. The goal of this study was to determine which knee angle allowed for the production of the greatest knee extensor maximal voluntary isometric torque (KEMVIT), the greatest electrically elicited torque, and the highest percent of KEMVIT from the knee extensor muscles. Case Description : Eighteen participants were secured in a force dynamometer with the knee positioned at 30°, 60°, and 90° flexion. Participants performed KEMVITs followed by electrically elicited contractions to their maximum tolerance. Outcomes : The mean ± SD of the peak KEMVITs was 123.7 ± 35.7 Nm, 222.6 ± 67.1 Nm, and 248.2 ± 81.1 Nm at 30°, 60°, and 90°, respectively. Significantly greater KEMVITs were produced at 60° and 90° than at 30° ( p < 0.001). The mean ± SD of the maximally tolerated electrically elicited torques was 71.8 ± 18.8 Nm, 170.9 ± 70.4 Nm, and 134.6 ± 72.6 Nm at 30°, 60°, and 90°, respectively. Significantly higher torques were tolerated at 60° than at 30° ( p < 0.001) and 90° ( p = 0.018). The mean ± SD of the percent KEMVITs was 59.7 ± 11.7%, 78.2 ± 23.8%, and 52.6 ± 18.7% at 30°, 60°, and 90°, respectively. Significantly greater percent KEMVITs were produced at 60° than at 30° ( p = 0.001) and 90° ( p < 0.001). Discussion : Electrically elicited quadriceps torque production is greater at 60° as compared to 30° and 90° knee flexion.